Electrospun cellulose acetate nanofiber upscaling with a metal plate needleless spinneret. (10th January 2020) - Wu, Jiajun; Quan, Zhenzhen; Zhang, Hongnan; Qin, Xiaohong; Wang, Rongwu; Yu, Jianyong
Abstract: Needleless electrospinning has been a simple preparation technique for nanofiber output upscaling. However, cellulose acetate (CA) has never been tried before for its high volatility in solvent acetone. By comparing the different solvent system of acetone/dimethyl sulfoxide (DMSO), acetone/dimethylacetamide (DMAc) and acetic acid/water, the electrospun CA nanofiber was successfully prepared via metal plate needleless spinneret. The results showed that electrospun CA nanofiber could be steadily and continuously obtained in acetone/DMSO = 2/1 v/v solvent system with output around 10–20 ml h −1 . The solution viscosity, conductivity and surface tension were measured with different amount of amphiphilic surfactant added. With higher amount of surfactant, the solution viscosity slightly decreased, and the conductivity increased steadily. The surface tension decreased to a stable constant with increasing surfactant amount. The correlation between the three independent variables and the average diameter and their CV value of electrospun CA nanofibers was investigated by SPSS Pearson partial correlation analysis. Solution viscosity was highly correlated with mean diameter. The linear regression analysis of the solution viscosity and the mean diameter of CA nanofibers was conducted. The predicted value of mean diameter of nanofibers had a high fitting goodness with the real value. Finally, the differences between electrospun CA nanofiber via single needle and needleless metal plate spinneret were also compared.